Targeting the Immune Complex–Bound Complement C3d Ligand as a Novel Therapy for Lupus - Kulik, Liudmila (J Immunol, 2019)
Humoral autoimmunity is central to the development of systemic lupus erythematosus (SLE). Complement receptor type 2 (CR2)/CD21 plays a key role in the development of high-affinity Abs and long-lasting memory to foreign Ags. When CR2 is bound by its primary C3 activation fragment–derived ligand, designated C3d, it coassociates with CD19 on B cells to amplify BCR signaling. C3d and CR2 also mediate immune complex binding to follicular dendritic cells. As the development of SLE involves subversion of normal B cell tolerance checkpoints, one might expect that CR2 ligation by C3d-bound immune complexes would promote development of SLE. However, prior studies in murine models of SLE using gene-targeted Cr2(−/−) mice, which lack both CR2 and complement receptor 1 (CR1), have demonstrated contradictory results. As a new approach, we developed a highly specific mouse anti-mouse C3d mAb that blocks its interaction with CR2. With this novel tool, we show that disruption of the critical C3d–CR2 ligand-receptor binding step alone substantially ameliorates autoimmunity and renal disease in the MRL/lpr model of SLE.